2015
DOI: 10.1210/en.2014-1393
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adrenergic Signaling Is Responsible for Decreased Glucose-Stimulated Insulin Secretion in the Chronically Hyperinsulinemic Ovine Fetus

Abstract: Insulin may stimulate its own insulin secretion and is a potent growth factor for the pancreatic β-cell. Complications of pregnancy, such as diabetes and intrauterine growth restriction, are associated with changes in fetal insulin concentrations, secretion, and β-cell mass. However, glucose concentrations are also abnormal in these conditions. The direct effect of chronic fetal hyperinsulinemia with euglycemia on fetal insulin secretion and β-cell mass has not been tested. We hypothesized that chronic fetal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…Further evidence for fetal β-cell hyper-responsiveness to glucose stimulation following inhibition of chronic adrenergic suppression was provided by experiments in near term control fetal sheep following 7–11 days of a chronic fetal insulin infusion where fetal hypoxemia and hypercatecholinemia developed and GSIS was completely attenuated. However, GSIS was completely restored to control levels during acute pharmacological adrenergic inhibition, (Andrews, et al 2015) similar to observations in PI-IUGR fetuses. Recently, we confirmed a direct role for chronically elevated norepinephrine concentrations in the development of β-cell hyper-responsiveness to glucose stimulation following acute discontinuation of adrenergic signaling.…”
Section: Pancreatic Developmentsupporting
confidence: 81%
“…Further evidence for fetal β-cell hyper-responsiveness to glucose stimulation following inhibition of chronic adrenergic suppression was provided by experiments in near term control fetal sheep following 7–11 days of a chronic fetal insulin infusion where fetal hypoxemia and hypercatecholinemia developed and GSIS was completely attenuated. However, GSIS was completely restored to control levels during acute pharmacological adrenergic inhibition, (Andrews, et al 2015) similar to observations in PI-IUGR fetuses. Recently, we confirmed a direct role for chronically elevated norepinephrine concentrations in the development of β-cell hyper-responsiveness to glucose stimulation following acute discontinuation of adrenergic signaling.…”
Section: Pancreatic Developmentsupporting
confidence: 81%
“…), or insulin imbalance (Andrews et al . ). Interestingly, an acute adrenergic blockade in the IUGR fetus revealed the development of this hyper‐insulin secretion response (Leos et al .…”
Section: Discussionmentioning
confidence: 97%
“…Blunted insulin secretion continues throughout the remainder of gestation and is inhibited in part by high concentrations of plasma catecholamines (Owens et al 2007a;Leos et al 2010;Macko et al 2016). In fact, similar inhibition occurred when hypercatecholaminaemia was induced in normally grown fetuses with an exogenous noradrenaline infusion (Chen et al 2014), acute maternofetal hypoxia (Jackson et al 2000;Yates et al 2012b), anaemic hypoxaemia (Benjamin et al 2017), or insulin imbalance (Andrews et al 2015). Interestingly, an acute adrenergic blockade in the IUGR fetus revealed the development of this hyper-insulin secretion response (Leos et al 2010;Macko et al 2013).…”
Section: Figure 8 Ex Vivo Glucose Oxidation Rates In Skeletal Musclementioning
confidence: 96%
“…In addition to overlap in receptor binding (Fowden ; Kulkarni ), we have previously demonstrated that chronic infusion of insulin into the fetal circulation increases arterial IGF‐1 concentrations by 30% (Andrews et al. ). Combined with our current study demonstrating a significant reduction in circulating insulin concentrations following chronic infusion of the IGF‐1 agonist and other studies (Fowden and Forhead ), it is clear these two anabolic hormones have a complex relationship for regulating each other and for regulating fetal growth.…”
Section: Discussionmentioning
confidence: 99%